2011
DOI: 10.1002/etc.670
|View full text |Cite
|
Sign up to set email alerts
|

Comparative toxicity of two glyphosate formulations (original formulation of Roundup® and Roundup WeatherMAX®) to six North American larval anurans

Abstract: The toxicity of two glyphosate formulations (the original formulation of Roundup® and Roundup WeatherMAX®) to six species of North American larval anurans was evaluated by using 96-h static, nonrenewal aqueous exposures. The 96-h median lethal concentration values (LC50) ranged from 1.80 to 4.22 mg acid equivalent (ae)/L and 1.96 to 3.26 mg ae/L for the original formulation of Roundup and Roundup WeatherMAX, respectively. Judged by LC50 values, four species were more sensitive to Roundup WeatherMAX exposures, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
1
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 23 publications
1
34
1
2
Order By: Relevance
“…The general lack of herbicide induced mortality contrasts with the majority of previously published studies conducted on other glyphosate-based herbicide formulations (Edginton et al, 2004;Howe et al, 2004;Relyea, 2004Relyea, , 2005 and laboratory studies conducted on Roundup WeatherMax (Fuentes et al, 2011;Williams and Semlitsch, 2010;Lanctôt et al, 2014). All of which found adverse effects on survival in the range of the high initial exposure concentrations used in this study.…”
Section: Direct Toxicity To Amphibian Larvaecontrasting
confidence: 82%
See 1 more Smart Citation
“…The general lack of herbicide induced mortality contrasts with the majority of previously published studies conducted on other glyphosate-based herbicide formulations (Edginton et al, 2004;Howe et al, 2004;Relyea, 2004Relyea, , 2005 and laboratory studies conducted on Roundup WeatherMax (Fuentes et al, 2011;Williams and Semlitsch, 2010;Lanctôt et al, 2014). All of which found adverse effects on survival in the range of the high initial exposure concentrations used in this study.…”
Section: Direct Toxicity To Amphibian Larvaecontrasting
confidence: 82%
“…Laboratory and mesocosm studies have demonstrated that exposure to some glyphosate-based herbicides results in increased mortality or effects on the growth and development of amphibian larvae at concentrations in the range predicted by worst case exposures (e.g., Edginton et al, 2004;Fuentes et al, 2011;Howe et al, 2004;Mann and Bidwell, 1999;Relyea, 2005;Williams and Semlitsch, 2010) indicating these herbicides pose a high risk to amphibian larvae in natural systems. However, negative effects have not been observed in the limited number of field experiments examining impacts of on either larval (Edge et al, 2012;Lanctôt et al, 2013;Thompson et al, 2004;Wojtaszek et al, 2004) or terrestrial life stages (Edge et al, 2011.…”
Section: Introductionmentioning
confidence: 99%
“…Embryos are approximately five times (96-h LC 50 value of 0.59 mg a.i./L; 95 % CIs 0.5, 0.7 mg a.i./L) and early larvae approximately 15 times (96-h LC 50 value of 0.09 mg a.i./L; 95 % CIs 0.07, 0.11 mg a.i./L) more sensitive to FO-UL than those of D. scovazzi (Wagner et al 2015). Such species-specific responses to herbicide exposure in anuran larvae have been previously reported (Anaxyrus americanus, A. boreas, A. fowleri, Crinia insignifera, Heleioporus eyrei, Hyla versicolor H. chrysoscelis, Limnodynastes dorsalis, Lithobates catesbeianus, L. clamitans, L. pipiens, L. sphenocephalus, L. sylvaticus, Litoria moorei, Pseudacris crucifer, P. triseriata, R. cascadae and X. laevis [Howe et al 1998;Mann and Bidwell 1999;Edginton et al 2004;Howe et al 2004;Relyea and Jones 2009;Williams and Semlitsch 2010;Fuentes et al 2011]). This could argue for X. laevis to be a good sentinel species for other anurans because embryos and larvae were often significantly more sensitive than early developmental stages of other anurans (see Bidwell 2000, 2001;Edginton et al 2004;Howe et al 2004).…”
Section: Comparison With the Pipid Anuran Model Organism X Laevismentioning
confidence: 80%
“…Tsui and Chu (2003) reported that, in general, Roundup® and the surfactant had a higher acute toxicity than technical-grade glyphosate and IPA for the aquatic microorganisms tested (bacteria, microalgae, protozoa, and crustaceans), with the surfactant accounting for about 46 % of Roundup® toxicity. Studies using amphibians agree that the surfactant contributes to the majority of the toxicity of the commercial formulation (Relyea and Jones 2009;Fuentes et al 2011;Moore et al 2012). …”
Section: Introductionmentioning
confidence: 97%